Long non-coding RNA H19 mediates mechanical tension-induced osteogenesis of bone marrow mesenchymal stem cells via FAK by sponging miR-138 - Wu, Jiajing; Zhao, Jing; Sun, Lian; Pan, Yongchu; Wang, Hua; Zhang, Wei-Bing (Bone (New York, N.Y.), 2018)
Bone marrow mesenchymal stem cells (BMMSCs) provide the biological basis for bone reconstruction. Mechanical tension stimulation as a potent modulator is able to promote osteogenic capability of BMMSCs. Long non-coding RNAs (LncRNAs) as competing endogenous RNAs (ceRNAs) for microRNAs, are postulated to regulate the osteogenic differentiation of stem cells. However, the mechanism how (whether) lncRNAs mediates tension-induced osteogenesis of BMSCs still remains poor understood. Here, human BMMSCs (hBMMSCs) were subjected to mechanical tension (10%, 0.5Hz). Results showed that mechanical tension could enhance osteogenic differentiation and increase H19 expression. H19 deficiency suppressed tension-induced osteogenic differentiation, demonstrating that H19 could mediate tension-induced osteogenesis in hBMMSCs. Besides, mechanical tension could suppress miR-138 expression, and down-regulated miR-138 promoted tension-induced osteogenesis in hBMMSCs. Luciferase reporter assays illustrated that H19 had binding sites with miR-138, and H19 deficiency increased miR-138 level, demonstrating that H19 may act as a ceRNA for miR-138 in hBMMSCs. Luciferase reporter assays also showed that miR-138 could target PTK2,a gene encoding focal adhesion kinase (FAK). Up-regulated miR-138 impaired increased FAK expression induced by mechanical tension. The relationship among H19, miR-138 and FAK under tension condition was further studied. H19 deficiency inhibited FAK expression, which could be partly rescued by knock-downing miR-138. In addition, suppressed tension-induced osteogenic differentiation in H19 defective cells was partly rescued by miR-138 knockdown. Taken together, this study indicated that H19 is a positive regulator in tension-induced osteogenesis of hBMMSCs through acting as a ceRNA for miR-138 and then up-regulating downstream FAK. •Mechanical tension could enhance osteogenesis of hBMMSCs.•Long non-coding RNA H19 mediates mechanical tension-induced osteogenesis.•H19 acts as a sponge to hijack miR-138 under tension strain.•H19 as ceRNA for miR-138 regulates tension-induced osteogenesis via downstream FAK.